2017
DOI: 10.4236/crcm.2017.68023
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospitalization for Long Stay Patients

Abstract: This case study described the structure and preliminary impact of a hospital program to improve efficiency by reducing long stays for adult medicine inpatients. The program focused resources on these patients, including an experienced case management staff, effective relationships with long term care providers, and Subacute and Complex Care services. The program caused the total number of adult medicine patient days associated with these patients to decline by 1593, or 4780 on an annual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Many studies found that comprehensive discharge planning is essential for delayed discharge related to family factors. [16][17][18][19][20] Hospital discharge preparation teams and social workers should address the difficulties faced by families and patients after discharge. All long-stay cases due to delayed discharge are preventable.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that comprehensive discharge planning is essential for delayed discharge related to family factors. [16][17][18][19][20] Hospital discharge preparation teams and social workers should address the difficulties faced by families and patients after discharge. All long-stay cases due to delayed discharge are preventable.…”
Section: Discussionmentioning
confidence: 99%